Peningkatan Daya Saing Produk UKM Kemuning Mandiri Desa Cogreg, Kabupaten Bogor - Apriani, Ari; Ramayanti, Desi; Komarudin, Komarudin; Elvaresia, Meysiel; Hutapea, Natalia (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
This community service program aims to enhance the competitiveness of the Kemuning Mandiri SME products in Cogreg Village, Bogor Regency, which faces challenges in marketing and branding. Utilizing methods that include socialization, packaging design training, and the utilization of e-commerce, this initiative focuses on product rebranding and the use of technology for production efficiency. The results achieved demonstrate a significant improvement in packaging design, making it more attractive and informative, thereby increasing product appeal. Additionally, members of the SME successfully marketed their products online through e-commerce platforms and social media. The implementation of automatic sealing machines has also greatly contributed to maintaining product quality and extending shelf life, enabling SME members to produce larger volumes without compromising quality. Furthermore, the food processor has assisted Kemuning Mandiri in increasing the production of lele nuggets. The implementation of this program has not only increased sales but also enhanced the capacity of SME members to manage their businesses effectively. It is expected that with ongoing support and collaboration, Kemuning Mandiri SME can continue to grow and make a positive contribution to the local economy.